Analysis Of Differential Equation Misconceptions Among Pre-Service Mathematics Teachers - Ika Meika; Asep Sujana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
Differential Equations (DE) is a fundamental course for pre-service mathematics teachers as it supports the development of advanced calculus understanding and mathematical modeling skills. Despite its importance, many studies report that students still experience misconceptions when understanding and solving DE problems. This study aims to analyze the types and causes of misconceptions among pre-service mathematics teachers in solving DE problems. A descriptive qualitative approach was employed involving 19 mathematics education students from two private universities in Banten. The research instruments consisted of misconception tests in the form of true–false and essay questions, in-depth interviews, and focus group discussions (FGDs). Data analysis was conducted through identifying errors, classifying misconception types, and triangulating data sources. The findings revealed that procedural misconceptions were the most dominant, with an average of 72.63%, followed by computational misconceptions at 67.37% and conceptual misconceptions at 54.74%. Procedural errors mainly occurred in applying separation of variables, performing integration, and checking exact conditions, while conceptual errors were related to understanding variable relationships and the meaning of DE solutions. These results indicate that students’ understanding remains fragmented and not fully integrated. Therefore, instructional strategies are needed that balance conceptual understanding, procedural mastery, and computational accuracy in Differential Equations learning.